IDENTIFICATION OF THE PHYTOCOMPONENTS IN LORANTHUS MICRANTHUS METHANOLIC EXTRACT BY GAS CHROMATOGRAPHY-MASS SPECTROMETRY - Igwe K. K.1*, Nwankwo P. O.,Otuokere I. E., Ijioma S .N., Amaku F.J. Chika Ikenga (International Journal of Research Science and Management, 2015)
Phytocomponents in methanolic extract of Loranthus micranthus leaf was studied using GC MS analysis. 12 compounds were identified from the extract. The major chemical constituents were cis-Octadecenoic acid (Peak area 44.82% ; RT 22.743), Octadecanoic acid ( 18.34% ; RT 18.34),Ethylhexanoate(Peak area 8.7% ; RT 32.142), Curcumin(1E,4Z,6E)-5-hydroxy-1-7- bis(4-hydroxy-3-methoxyphenyl)hepta-1,4,6-trien-3-one (Peak area 7.25% ; RT 27.456),1,3-Hexyloxacyclotridec-10-en-2-one (Peak area 5.34% ; RT 21.382). The bioactive compounds in the methanolic leaf extract of Loranthus micranthus exhibited phytopharmacological significance and hence could be of therapeutic use against some diseases.